Assessment of oil pollution of the soil in the territory of sewage Atyrausky oil refinery (Eurasian Journal of Ecology, 2016)
In this article results of researches of extent of environmental pollution by oil, oil products and hydrogen sulfide in soils of coastal zones of Atyrau oil refinery are presented to Atyrau.
Keywords: soil; pollution; oil products; hydrogen sulfide